Alkaptonuria in Turkey: Clinical and molecular characteristics of 66 patients - ÖZTÜRK HİŞMİ, BURCU (ELSEVIER, 2021)
Alkaptonuria (AKU) is an inborn error of metabolism caused by the deficiency of homogentisate 1,2-dioxygenase (HGD) as a result of a defect in the HGD gene. HGD enzyme deficiency results in accumulation of homogentisic acid (HGA) in the body, which in turn leads to multisystemic clinical symptoms. The present study aimed to investigate the presenting symptoms, age at diagnosis, and clinical and genetic characteristics of AKU patients followed-up in different centers in Turkey. In this cross-sectional, multicenter, descriptive study, medical records of 66 AKU patients were retrospectively evaluated. Patients? data regarding demographic, clinical and genetic characteristics were recorded. HGD database (http://hgddatabase.cvtisr.sk/) was used to identify HGD gene variants. Of the patients, 37 (56.1%) presented with isolated dark urine and 29 (43.9%) were diagnosed based on the clinical symptoms or family screening. One of these patients was on follow-up for 2 years due to Parkinsonism and was diagnosed with AKU on further analyses. Signs of ochronosis such as joint pain, low back pain and renal stones developed in childhood in 7 patients. Eight patients were diagnosed with depression via psychiatric evaluation. There were 14 (21.2%) patients operated on for ochronosis. The most frequent mutation observed in the patients was c.175delA, which was followed by c.674G > A and c.1007-2A > T mutations. Four novel mutations (c.189G > A, c.549+1G > T, c.1188+1G > A, and c.334 T > G) were identified in the patients included in the study. In addition to the known signs such as dark urine and skin pigmentation, symptoms involving different systems such as neurological findings and depression can also be encountered in AKU patients. The presence of a change in urine color needs to be questioned in patients presenting with different symptoms such as arthralgia/arthritis, renal stones or low-back pain, particularly in childhood, when skin ochronosis is not pronounced, and further examination should be performed.
Keywords: Alkaptonuria; Children; Adults; Ochronosis; HGD gene; Mutation